2018
DOI: 10.1159/000487044
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of MicroRNA-495 Derepressed PTEN to Effectively Protect Rat Cardiomyocytes from Hypertrophy

Abstract: Background: The effect of microRNA (miR)-495 on cardiomyocyte hypertrophy was explored by investigating the expression of proteins in the phosphatidylinositol 3-kinase (PI3K)/Akt signal pathway. Methods: The study used a rat model of pulmonary arterial hypertension (PAH) induced by monocrotaline (MCT) administration (60 mg/kg) for 2 weeks. Arterial wall thickness and right ventricular hypertrophy were examined by hematoxylin and eosin (HE) staining in the lungs and hearts. The expression level of miR-495 and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Important miRNAs involved in the cardiac hypertrophy are also miRNA-22 (influence phosphatidylinositol-3-kinase (PI3K)-protein kinase B (AKT)) [100], miRNA-212/132 family (active through antihypertrophic FoxO3 transcription factor), or miRNA-199 (miRNA-199a targets the pro-autophagic and antihypertrophic factor glycogen synthase kinase 3β; miRNA-199b acts through targeting tyrosine phosphorylation regulated kinase 1A (Dyrk1a) gene, involved in the phosphorylation of NFAT factors) [101][102][103]. Other studies dealing with miRNAs associated with cardiac hypertrophy observed changed expression of miRNA- 21, -18b, -195, -199, -29, -22, or -23 levels [104-107].…”
Section: Cardiac Hypertrophymentioning
confidence: 99%
“…Important miRNAs involved in the cardiac hypertrophy are also miRNA-22 (influence phosphatidylinositol-3-kinase (PI3K)-protein kinase B (AKT)) [100], miRNA-212/132 family (active through antihypertrophic FoxO3 transcription factor), or miRNA-199 (miRNA-199a targets the pro-autophagic and antihypertrophic factor glycogen synthase kinase 3β; miRNA-199b acts through targeting tyrosine phosphorylation regulated kinase 1A (Dyrk1a) gene, involved in the phosphorylation of NFAT factors) [101][102][103]. Other studies dealing with miRNAs associated with cardiac hypertrophy observed changed expression of miRNA- 21, -18b, -195, -199, -29, -22, or -23 levels [104-107].…”
Section: Cardiac Hypertrophymentioning
confidence: 99%
“…Non-coding RNAs (microRNAs) mediate cardiac hypertrophy (microRNA-22, microRNA-495 and several more) [ 126 128 ] and fibrosis (microRNA-433) [ 129 ], and as such may represent important biomarkers of HF. Also, they can be used to differentiate between reduced and preserved ejection HF, as well as determine prognosis.…”
Section: Novel Cardio-oncology Biomarkers Under Investigationmentioning
confidence: 99%
“…Its cardiac-specific deletion in mouse was sufficient to blunt hypertrophy and cardiac remodeling in the presence of stressors, such as isoproterenol and activated calcineurin transgene [37]. Additionally, miR-22 overexpression in neonatal rat cardiomyocytes increased cell size and induced hypertrophic markers, such as the natriuretic peptide A ( Nppa ) gene, while knockdown of miR-22 attenuated the hypertrophy induced by phenylephrine, isoproterenol or angiotensin II (Ang-II) [45]. The Authors showed that miR-22 might influence CH by Pten inhibition, possibly involving phosphatidylinositol-3-kinase (PI3K)-protein kinase B (AKT) [45].…”
Section: Hypertrophymentioning
confidence: 99%